First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea